Brachial-ankle pulse wave velocity increasing with heart rate accelerates - Qian Wang; Xinxin Xu; Xue Geng; Haijuan Hu; Wei Cui (Frontiers in Cardiovascular Medicine, 2023)
Pulse wave velocity (PWV) indicates the degree of vascular stiffness. This study aimed to explore the association between heart rate (HR) and brachial-ankle (ba)-PWV in patients with pacemaker implantation. This retrospective observational study included patients who underwent permanent pacemaker implantation at the Second Hospital of Hebei Medical University between December 2018 and December 2021. All patients were pacemaker-dependent, and the ba-PWV values were collected during HR setted from 60 to 100 bpm. A total of 68 patients (34 males, aged 65.97 ± 9.90 years) were included in this study. There were significant difference of ba-PWV and diastolic blood pressure (DBP) among different HR (both P < 0.001). After adjusted systolic blood pressure (SBP), DBP, age, and sex, the generalized estimating equation showed ba-PWV was independently associated with HR, with increased HR showed higher coefficient: 70 bpm: β = 42.26 (95% CI: 15.34–69.18, P = 0.002), 80 bpm: β = 84.16 (95% CI: 52.48–115.84, P < 0.001), 90 bpm: β = 129.27 (95% CI: 52.48–115.84, P < 0.001), and 100 bpm: 186.31 (95% CI: 137.02–235.59, P < 0.001). The results demonstrate that changes in HR may affect the ba-PWV, the ba-PWV values tend to be higher when HR accelerates.